Social Work Education Canada’s North: Capacity Building through Social Work (Journal of Comparative Social Work, 2012)
The Faculty of Social Work program at the University of Regina is a broker for two social work programs north of the 60th parallel reaching the northern residents of both Aboriginal and non-Aboriginal ancestry. In addition, for over 30 years, the University of Regina partners with the First Nations University of Canada where a specialized Bachelor of Indian Social Work is offered and now a Master of Aboriginal Social Work. This paper presents the background to the Northern Human Service/BSW program at Yukon College in Whitehorse, Yukon and the Certificate of Social Work at the Aurora College in Yellowknife, Northwest Territories.